THE ANALYSIS OF THE FLORAL DESIGN OF PRESCHOOL EDUCATIONAL INSTITUTIONS ON THE EXAMPLE OF DNIPRO CITY - Mylnikova, Olga; Ilchenko, Larysa (Theory and practice of design, 2025)
The article analyzes the flower design of 3 municipal institutions of preschool education in Dnipro. The purpose is to determine the type and range of flower beds in the kindergartens of Residential area “Western” with recommendations for optimizing their species composition. Methodology. Methods of route and visual examinations, analysis and comparison have been applied. The flower garden project is created in the program Realtime Landscaping Architect. Results. According to the reduction of floral species, the establishments were located as follows: kindergarten № 182> № 241> № 233. Among the 42 identifiedspecies of decorative herbaceous plants, 8 common species were recorded for the floral design of the surveyed kindergartens. Annuals, biennials, and perennials are involved in arranging flower beds as the only defined type of flower garden. The priority of using perennial flower species on the territory of all institutions has been established with a predominant share of 83.3%, which is projected in terms of saving money and time. It was noted that some representatives of the Hosta genus are not compatible with growing conditions, and it was proposed to expand their range, based on the decorative leaves. Tips for diversifying flower beds of solar locations and renewal of landscape for shady corners of preschool institutions with a list of relevant plants were provided. It is recommended to systematize individual flower beds by dividing vegetables and decorative flora, as well as to get rid of the poisonous plants of Convallaria majalis and Polygonatum odoratum. The project of the flower garden for the front part of the institution № 182 was developed with the involvement of Cineraria maritima, Sedum spectabile, Tagetes patula, Ageratum houstonianum, Coleus х hybridum. The criteria for selecting the proposed species are substantiated. A promising direction for further research is the analysis of options for arranging floral decoration in preschool institutions in other administrative districts of Dnipro. Scientific novelty. For the first time the species range of ornamental herbaceous plants of individual kindergartens in Dnipro has been determined and an original design for a flower garden for one of them has been proposed. Practical relevance. The results obtained can serve as a basis for optimizing floral design on the territory of the surveyed kindergartens in order to increase its functionality and aesthetic appeal.